Hydrogen peroxide bleaching of cotton in ultrasonic energy - YÜKSELOĞLU, SEVHAN MÜGE (ELSEVIER SCIENCE BV, 2005)
It is well known that, conventional hydrogen peroxide bleaching process is an important and a specific step for wet processors; however it has some problems such as long time, high energy consumption. On the other hand, using ultrasonic energy in bleaching is an alternative method for the conventional processes. In this work, 100% cotton materials of different forms such as raw fibre, ring-spun yarns and knitted fabrics produced from these cottons, were treated with hydrogen peroxide in two different concentrations (5 mL/L and 10 mL/L), at three different temperatures (20 degrees C, 30 degrees C, 40 degrees C) and times (20 min, 30 min, 60 min). Whiteness Index of the samples were then measured spectrophotometrically and the overall results were compared. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen peroxide; conventional bleaching; cotton; fibre; yarn; knitted fabric; ultrasonic energy; whiteness index